Penerapan Model Antrian Multi Channel-Single Phase pada SPBU Sempu Jurong Cikarang Utara - Hoerunisa, Ica; Sukanta, Sukanta (UNISTEK, 2021)
SPBU Sempu Jurong provides 4 service facilities and two of them are service facilities for two-wheeled vehichles which have the most dominant queues compared to the entire queue of the existing system. The queue that occurs is due to the unbalance between the number of service facilities and the number of two-wheeled vehicle customers. This study aims to increase the level of service by knowing the number of service facilities and service time at optimal level at SPBU Sempu Jurong. In this study, the method used is the Multi Channel-Single Phase queuing model. The results of this research indicate that the addition of one facility line causes the service time required for SPBU Sempu Jurong for two-wheeled vehicle refueling services to be faster. Based on calculations using the Multi Channel-Single Phase model, it is obtained that the service time with 2 lines of service facilities is 0.291 minutes, while the optimal service time needed with 3 lines of facilities takes the longest of 0.027 minutes. This shows that it is optimal because the speed of time in service can be improved so that customer satisfaction of two-wheeled vehicles with services at SPBU Sempu Jurong Cikaran Utara can be achieved.